Genetic diversity of the coral-euendolithic algae Ostreobium along the depth at the Southwestern Caribbean (2021)
Ostreobium is considered the most pervasive microbioeroder in coral reefs, which is a serious threat to the structural integrity of the coral reef. On the other hand, it translocates photoassimilates to the coral tissue, increasing host resilience under bleaching events than lead corals to death. Improving our knowledge on the complex associations between corals and euendolithic partners will help us to better predict how coral reef ecosystems will respond to future environmental stressors threatening ecosystem maintenance. The present study investigated the genetic patterns in Ostreobium euendolithic algae found associated to common corals present at two different localities in the Colombian Caribbean. Using the barcode rbcL marker, we reveal a high diversity of algae with complex associations by host, geographical location, depth-related variables (e.g., light penetration, temperature) and micro niche factors such skeletal density of coral host. Overall, we found a tight association between locality and Ostreobium clades, ¿low¿ and ¿high¿ irradiance habitats, and high/low temperature clusters in distribution of diversity composition. Moreover, most of the Ostreobium clades found exhibits specificity by host.